Identification of salt stress-tolerant candidate genes in the BC2F2 population at the seedling stages of G. hirsutum and G. darwinii using NGS-based bulked segregant analysis - Shehzad, Muhammad; Ditta, Allah; Cai, Xiaoyan; Ur Rahman, Shafeeq; Xu, Yanchao; Wang, Kunbo; Zhou, Zhongli; Fang, Liu (Frontiers in Plant Science, 2023)
Salinity is a major threat to the yield and productivity of cotton seedlings. In the present study, we developed a BC2F2 population of cotton plants from Gossypium darwinii (5–7) and Gossypium hirsutum (CCRI 12–4) salt-susceptible parents to identify salt-resistant candidate genes. The Illumina HiSeq™ strategy was used with bulked segregant analysis. Salt-resistant and salt-susceptible DNA bulks were pooled by using 30 plants from a BC2F2 population. Next-generation sequencing (NGS) technology was used for the sequencing of parents and both bulks. Four significant genomic regions were identified: the first genomic region was located on chromosome 18 (1.86 Mb), the second and third genomic regions were on chromosome 25 (1.06 Mb and 1.94 Mb, respectively), and the fourth was on chromosome 8 (1.41 Mb). The reads of bulk1 and bulk2 were aligned to the G. darwinii and G. hirsutum genomes, respectively, leading to the identification of 20,664,007 single-nucleotide polymorphisms (SNPs) and insertions/deletions (indels). After the screening, 6,573 polymorphic markers were obtained after filtration of the candidate regions. The SNP indices in resistant and susceptible bulks and Δ(SNP-index) values of resistant and susceptible bulks were measured. Based on the higher Δ(SNP-index) value, six effective polymorphic SNPs were selected in a different chromosome. Six effective SNPs were linked to five candidate genes in four genomic regions. Further validation of these five candidate genes was carried out using reverse transcription-quantitative polymerase chain reaction (RT-qPCR), resulting in an expression profile that showed two highly upregulated genes in the salt-tolerant species G. darwinii, i.e., Gohir.D05G367800 and Gohir.D12G239100; however, the opposite was shown in G. hirsutum, for which all genes, except one, showed partial expression. The results indicated that Gohir.D05G367800 and Gohir.D12G239100 may be salt-tolerant genes. We are confident that this study could be helpful for the cloning, transformation, and development of salt-resistant cotton varieties.